(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The production of particleboard is influenced by various technological and technical factors that affect both quality and economic performance. Among these, board density is particularly important-higher density enhances mechanical properties but increases production costs. Therefore, medium-density particleboards are typically manufactured from softwood species, whose low density provides favorable strength characteristics. In contrast, hardwood species often reduce mechanical performance, limiting their proportion in the mixture to 20–30%. However, in the Republic of Bulgaria, 32% of forested areas are covered with oak species, including 9% with turkey oak (Quercus cerris L.), making its exclusion from production impractical. This study explores the potential for greater use of turkey oak in three-layer particleboards made from aspen. Layers of turkey oak particles were added to the face layers at 10%, 20% and 30%. In two additional panels, turkey oak was included in the core layer at 10% and 20%, resulting in a total content of 40% and 50%. The panels were manufactured under laboratory conditions at 180°C, 2.3 MPa and 330 seconds, with a target density of 640 kg·m⁻³. The results showed consistently high values of modulus of rupture and modulus of elasticity at all levels of turkey oak inclusion.